The attitudes and treatment practices of Hungarian primary care dentists regarding dental care for patients with haemophilia - Kitti Sipos; Ildikó Márton; Marianna Móré; Attila Csaba Nagy; Csongor Kiss (Scientific Reports)
Abstract Patients with haemophilia (PWH) frequently encounter difficulties in accessing dental services, yet research into dental professionals’ attitudes is limited. The present study was thus undertaken to investigate the attitudes and treatment practices of Hungarian dentists in the dental management of PWH. A cross-sectional survey was conducted between September 2022 and December 2022 among dentists working in the primary care sector. An anonymous self-administered questionnaire was utilized for data collection. Pearson’s Chi-squared test and Fisher’s exact test were used for statistical analysis. Variables with statistical significance (p < 0.05) were included in multiple logistic regression analyses. A total of 162 dentists consented to participate in the study. Most respondents (n = 113, 70%) reported a lack of both confidence and information about treating PWH. The study found that male gender (OR: 3.43, 95% CI: 1.49–7.90), experience in treating PWH (OR: 4.06, 95% CI: 1.73–9.52) and additional qualifications (PhD or DSc) beyond a basic dental degree (DMD/DDS) (OR: 9.40, 95% CI: 1.10-80.48) significantly influenced confidence. Dentists with a minimum of five years of experience demonstrated a greater degree of caution when performing procedures in a primary dental care setting when compared to their younger counterparts. Dental practitioners should receive support to manage PWH confidently.